Poluição plástica dos oceanos: desafios e oportunidades para o PET - Lucci, Vitória Bortolin (Universidade Federal de São Carlos, 2024)
With increasing demand and production, plastic poses a serious threat to the marine environment, with a particular focus on PET - poly(ethylene terephthalate), which constitutes, for example, food and beverage packaging and, due to its low biodegradability, accumulates in oceans, becoming a major source of pollution. Given this scenario, this study aims to analyze potential degradation pathways of plastic materials in the sea, with a specific focus on PET degradation, the influencing factors in each reaction, and their consequences. Additionally, the current recycling methods for such materials are discussed, along with their respective advantages and disadvantages. Finally, solutions adopted by major brands like adidas, H&M, and Levi’s in utilizing recycled polyester are presented. Through this study, it becomes evident that there are significant challenges in recycling plastic waste, from improper disposal to various degradation processes leading to fragmentation and loss of properties. However, there are pathways enabling the production of value-added products from recycled polyester, as exemplified by initiatives of the organization Parley for the Oceans, emphasizing sustainable product development using plastics found in oceans. Therefore, despite economic and technological challenges, PET recycling is crucial for reducing plastic pollution and safeguarding marine ecosystems, necessitating technological improvements and sustainable waste management.
Plastic pollution of the oceans: challenges and opportunities for PET
Keywords: PET - poli(tereftalato de etileno); Poluição marinha; Degradação plástica; Reciclagem; Sustentabilidade; PET - poly(ethylene terephthalate); Marine pollution; Plastic degradation; Recycling; Sustainability; ENGENHARIAS::ENGENHARIA DE MATERIAIS E METALURGICA::MATERIAIS NAO METALICOS